Pengaruh User Interface Pada Platform Digital Shopee Terhadap Shopping Enjoyment Customer Dalam Paradigma Information Foraging Theory - Sabar Sabar; Rosiana Eka Dewi; Teofilus; Gladys Greselda Gosal; Auditia Setio Budi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
The success of a digital platform can be seen from how many users visit the platform in one month. Users will visit digital platforms due to various factors, such as an attractive and easy-to-navigate user interface, satisfying digital service platforms, effectiveness in finding information, ease of payment, delivery of various goods, as well as platform security in storing data. The more users who visit digital platform will affect the level of product purchases. This research was conducted to examine the effect of the user interface on the Shopee digital platform in Indonesia on customer shopping enjoyment which is influenced by gender and mediation by the flow experience variable. Information Foraging Theory was chosen as the scalpel in this research because it is considered important to be considered as a priority for digital platforms in improving performance on their platforms. The research method used is a quantitative method and a purposive sampling method which is processed using the SPSS (Statistical Product and Service Solutions) application for Shopee users in Indonesia. The number of samples targeted in this study were 600 respondents who came from active students and alumni from UI, ITB, UGM, Unair, and ITS who often use the Shopee digital platform as a platform for online purchases.